The Relationship Between Knowledge of Major Affirmation and Vocabulary Mastery with The Ability to Write Exposition Texts in Junior High School Students - Suhartana, I Nengah; Jaya, Wayan Satria; Sutiyono, Akhmad (IJLHE: International Journal of Language, Humanities, and Education, 2018)
This study aims to determine the relationship between knowledge of affirmation and vocabulary mastery with the skills of writing expository texts in class VIII students of SMPN 2 Bandar Mataram To achieve the research objectives above, the data was collected after all the events in question took place. The techniques used in collecting research data are questionnaires, tests, and observations. Research data analysis techniques include analysis requirements test, normality test, and research hypothesis testing techniques. Based on the results of the study it can be concluded that, (1) there is a negative relationship between knowledge of assertiveness and skills in writing expository texts, indicated by a regression coefficient of 0.914. (2) there is a positive and significant relationship between vocabulary mastery and expository text writing skills as indicated by the regression coefficient of 0.860. (3) there is a positive and significant relationship between vocabulary mastery and the skill of writing exposition texts as indicated by the regression coefficient of 0.525 but has no effect on the variable knowledge of figurative language assertion. Based on the table, it can also be seen that the regression coefficient of the mastery of affirmation variable (X1) is -0.042, which means that if the mastery of affirmation increases 1 value, the result of writing students' exposition text (Y) will decrease by 0.042. The coefficient is negative, meaning that there is a negative relationship between the students' mastery of affirmation knowledge and the skills of writing expository texts.